The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.01.20.524764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutrient-regulated dynamics of chondroprogenitors in the postnatal murine growth plate

Abstract: Longitudinal bone growth relies on endochondral ossification in the cartilaginous growth plate where chondrocytes accumulate and synthesize the matrix scaffold that is replaced by bone. The chondroprogenitors in the resting zone maintain the continuous turnover of chondrocytes in the growth plate. Malnutrition is a leading cause of growth retardation in children; however, after recovery from nutrient deprivation, bone growth is accelerated beyond the normal rate, a phenomenon termed catch-up growth. Though nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 57 publications
(65 reference statements)
1
10
0
Order By: Relevance
“…The retention of EdU + cells in the RZ during the early phase of the recovery (Fig. 5b) resembled the enhanced self-renewal of Axin2 + chondroprogenitors observed during transient diet restriction in juvenile mice 28 . Since the capability of self-renewal in chondroprogenitors has been shown to appear only at postnatal stages 35 , one possible explanation was that self-renewal had been precociously activated upon injury.…”
Section: Compensatory Cartilage Growth Is Driven By Shifts In the Pro...supporting
confidence: 61%
See 3 more Smart Citations
“…The retention of EdU + cells in the RZ during the early phase of the recovery (Fig. 5b) resembled the enhanced self-renewal of Axin2 + chondroprogenitors observed during transient diet restriction in juvenile mice 28 . Since the capability of self-renewal in chondroprogenitors has been shown to appear only at postnatal stages 35 , one possible explanation was that self-renewal had been precociously activated upon injury.…”
Section: Compensatory Cartilage Growth Is Driven By Shifts In the Pro...supporting
confidence: 61%
“…1b"). As mentioned above, the latter scenario was recently found in the case of catch-up growth induced by transient diet restriction 28 . In ), using up their potential faster (eventually failing to catch-up).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The chondrocytespecific Igf1 knockout mouse demonstrated a reduction in postnatal body and femur length, and the chondrocyte-specific Igf1r knockout mouse demonstrated a significant reduction in bone growth, as well as a decrease in both growth plate proliferative and hypertrophic zone (Govoni et al, 2007;Wang et al 2011). A recent study revealed that resting zone chondrocytes in the growth plate serve as a major source of local IGF and activate the p-AKT pathway via autocrine and paracrine IGF signaling (Oichi et al, 2023). The study further revealed that cells that constitute bone and bone marrow, apart from chondrocytes, do not express Igf1, making chondrocytes the solitary source of local IGF.…”
Section: Disruption Of Chondrocyte-derived Igf Signaling In Smn2 1-co...mentioning
confidence: 99%